A chrome coating from a trivalent chromium bath containing extremely low concentration of Cr3+ ions. (2016) - Katırcı, Ramazan
In this study, the effects of saccharine on physical and chemical properties of Cr electrodeposition were investigated using electrochemical methods (linear voltammetry and impedance) and surface analysis methods [scanning electron microscopy equipped with energy-dispersive X-ray spectroscopy (SEM-EDS)]. According to voltammetric and EIS measurement results, saccharine shifted Eonset to the negative area, which hinder the evolution of H2 gas and decrease the charge transfer of Cr coating, which increase the efficiency of Cr coating. According to the SEM results, it was found that saccharine increased the number of cracks on the surface. The most important result of this study is that saccharine makes Cr coating possible in the extremely low concentration of Cr 3+ ion in a trivalent Cr bath.